Quiet please! Adverse effects of noise on child development - Anna Makles; Kerstin Schneider (University of Wuppertal, Schumpeter School of Business and Economics, 2016)
Noise pollution is detrimental to health and to cognitive development of children. This is not only true for extreme levels of noise in the neighborhood of an airport but also to traffic noise in urban areas. Using a census of preschool children, we show that children who are exposed to intensive traffic noise significantly fall behind in terms of school readiness. Being exposed to additional 10 dB(A) compares to about 3 months in kindergarten. We contribute to the lit-erature and the policy debate by working with administrative data and focusing on everyday exposure to noise. The proposed method is easily applied to other regions. We assess the public costs of different abatement instruments and compare the costs to the benefits. It turns out that the commonly used abatement measures like quiet pavement or noise protection walls in densely populated areas of about 3,000 to 5,000 inhabitants per km2 can be cost efficient, even with a conservative assessment of the benefits.
urn:nbn:de:hbz:468-20160609-114831-3
Keywords: Q53; I18; I26; H23; H54; 330; noise; child development; early education; abatement; abatement costs